Subsistence to commercial: urban farming transformation builds food security and social empowerment - Ilham Nur Hanifan Maulana; Chandra Dinata; Aditya Chisabul Amali; Ditania Arya Dewi (JRTI (Jurnal Riset Tindakan Indonesia), 2024)
This study aims to examine the potential of urban farming as a catalyst for diverse food security in densely populated areas, with a specific focus on Sukun Village, Malang City. The research seeks to identify how urban agriculture not only increases local food availability but also functions as an instrument for community empowerment through commercialization schemes. Sukun Village was selected due to its demographic density and existing urban farming initiatives, which provide a relevant context for studying these dynamics. Using a qualitative approach grounded in case study methodology, this study collected data through in-depth interviews with 15 key stakeholders, participatory observations at local farming sites, and analysis of policy documents and activity records related to urban farming at Rumah Alam Jaya. This approach ensures a comprehensive understanding of urban farming activities and their socio-economic impacts. The findings indicate that urban farming contributes to micro-food security by providing a consistent supply of fresh produce while fostering social solidarity and increasing household incomes. Specific examples include cooperative farming models and revenue streams from agrotourism activities. Furthermore, this study highlights the integration of urban farming with educational tourism as a strategic innovation to enhance the economic sustainability and attractiveness of urban agriculture. Practically, the results offer actionable insights for policymakers and practitioners aiming to support diverse and sustainable local food security through urban agricultural innovation. By strategically combining empowerment schemes with educational tourism, urban farming can be a viable solution to address food security challenges in urban areas. This research strengthens the literature on micro-food security and provides a replicable framework for integrating urban farming into community empowerment initiatives.